Avant-Propos - David Fée; Romain Garbaye (Revue Française de Civilisation Britannique)
The 2005 general election produced remarkable results that surprised many, and in more ways than one it seems to have ushered in a new era in British politics. Against all odds, the Conservatives scored an unexpectedly clear-cut victory which was matched by the scale of Labour’s defeat. What makes the election even more remarkable is the extent to which these results came as a surprise to most of those involved. Indeed, the most commonly expected outcome during the campaign had been a narrow victory for one of the two big parties or a hung parliament. Of course, this can be put down to the inability of pollsters to come close to an accurate prediction of the results. But it would be a particularly serious omission in the case of this particular election to overlook an obvious factor: the electoral campaign. This is the object of this special issue.